Walsh, Daphne. New Perlican Photograph of a woman and child. - Barrett, Terra
A photograph of Leah (Warren) Hobbs (right) and Ray (left). Above the photo says "Family Memories" and below the photo says "Mom & Ray." The photograph was printed by Kodak.